Synthesis, crystal structure, cholinesterase inhibitory activity, evaluation of insecticidal activities, and computational studies of new phosphonic acids - Gholivand, Khodayar; Mohammadpanah, Fahimeh; Yaghoubi, Rouhollah; Rahimzadeh Dashtaki, Maryam; Pooyan, Mahsa; Rahmani, Hamidreza; Roshanian, Zahra; Sharifi, Mahboobeh; EbrahimiValmoozi, Ali Asghar; Roohzadeh, Roohollah (Molecular diversity, 2022)
In an attempt to obtain the modified and novel insecticides with low human toxicity, a series of novel mono-, bis-, and tetraphosphonic acid derivatives were designed and characterized by infrared, 1 H, 13 C, and 31 P NMR spectroscopy and X-ray crystallography. The inhibitory effects of the synthesized compounds were evaluated using the in vitro Ellman method on human and insect acetylcholinesterase (AChE). Some of these compounds, which had low human and high insect toxicity, were chosen to assess the killing effects (in vivo) on third larval instar of elm leaf beetle (X. luteola). In vivo and in vitro evidence has revealed that bisphosphonic acids, containing hydrophobic systems, have a good selectivity of insect AChE inhibition. In the present study, docking results showed that bisphosphonic acids had lower binding energy and higher inhibition compared with tetraphosphonic acids due to the type of their topology and the ability of their hydrogen to interact with the catalytic triad (the main active site of the enzyme). Additionally, the QSAR results demonstrated that the major effecting factors on the insecticidal activity of the subject compounds are the hydrophobicity, size, shape, and ability to form a hydrogen bond. The present study can be helpful in the development of new insecticides. Graphic abstract